Outcomes and Predictors of Stimulant Misuse in College Students with and Without ADHD. Issue 5 (March 2022) - Francis, Alyssa R.; Weyandt, Lisa L.; Anastopoulos, Arthur D.; DuPaul, George J.; Shepard, Emily
In recent years, rates of prescription stimulant misuse have increased among young adults ages 18 to 25 along with increases in dispensing rates of these medications. Preliminary studies suggest that college students with Attention-Deficit Hyperactivity Disorder (ADHD) may be more likely to misuse their stimulant medication than their non-ADHD peers. Research is needed to further explore possible rates, correlates, and outcomes of prescription stimulant misuse among college students with and without ADHD. Data regarding study strategies, psychological functioning, stimulant misuse, and GPA were collected from students from universities within the US ( N = 144), showing significantly higher rates of misuse among college students with ADHD. With depression and anxiety entered into the predictive model, inattentive symptoms were the only significant predictor of misuse in the full sample. The present findings have implications for academic interventions aimed at supporting the success of college students with and without ADHD and inform academic outcomes of prescription stimulant misuse.